2020
DOI: 10.1177/0956797620929979
|View full text |Cite
|
Sign up to set email alerts
|

On Intersectionality: How Complex Patterns of Discrimination Can Emerge From Simple Stereotypes

Abstract: Patterns of discrimination are often complex (i.e., multiplicative), with different identities combining to yield especially potent discrimination. For example, Black men are disproportionately stopped by police to a degree that cannot be explained by the simple (i.e., additive) effects of being Black and being male. Researchers often posit corresponding mental representations (e.g., intersectional stereotypes for Black men) to account for these complex outcomes. We suggest that complex discrimination can be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 20 publications
(24 reference statements)
0
16
1
Order By: Relevance
“…Recent research on intersectionality has demonstrated how discrimination can emerge from simple stereotypes using a threshold model approach (Hester et al, 2020). In line with Hester et al (2020)’s argument, our results suggest that even though two individuals are similar in many respects, stereotypes can make one individual less likely to reach the threshold for success compared to another individual. Thus, even though a black female and white female share similar characteristics, certain stereotypes (e.g., angry black woman stereotype) can make it more challenging for the black female to reach the threshold for high competence, therefore potentially triggering poor performance evaluations and assessments of leadership capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on intersectionality has demonstrated how discrimination can emerge from simple stereotypes using a threshold model approach (Hester et al, 2020). In line with Hester et al (2020)’s argument, our results suggest that even though two individuals are similar in many respects, stereotypes can make one individual less likely to reach the threshold for success compared to another individual. Thus, even though a black female and white female share similar characteristics, certain stereotypes (e.g., angry black woman stereotype) can make it more challenging for the black female to reach the threshold for high competence, therefore potentially triggering poor performance evaluations and assessments of leadership capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, sexual LGB orientation or transsexual and transgender people also experience discrimination due to sexist attitudes and behaviors [ 6 ]. Sexism, along with other axes of oppression, such as racism, class, disability, homophobia and transphobia, gives rise to multiple forms of discrimination [ 7 ]. Sexist attitudes, behaviors and values generate gender inequalities that are manifest in the social structure and in interpersonal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…We can tease apart what it means to be both larger‐bodied and brown‐skinned; or to be larger‐bodied and a woman of a certain age; or to be larger‐bodied and identify as a minority sexually. Precisely defining the physical ideal relative not just to weight, but other demography as well, captures most accurately the lived experiences of those in a larger‐bodied body, where, potentially, objectified identities additively (or, frustratingly, multiplicatively) offer advantage or disadvantage (Hester, Payne, Brown‐Iannuzzi, & Gray, 2020; Mason, 2012; Moore‐Berg & Karpinski, 2021) and varying degrees of legal protection (Johnson, Roberto, et al., 2021). Weight, then, can be viewed by researchers as a factor that amplifies already‐afforded social privilege to certain groups and, conversely, perhaps its privilege amounts to not much (i.e.…”
Section: Foreground: Weight‐based Stigma Through the Lens Of Objectif...mentioning
confidence: 99%